Third Annual Fresno County Young Lawyers Hopper Luncheon with Justice Allen Broussard - Watkins, Howard::::::::: (1984)
Associate Justice Allen Broussard shaking hands with Jody Dupuis, former law clerk to Justice George Hopper Luncheon at Golden State Plaza ballroom: ceramic artwork on wall